2018
DOI: 10.1016/j.jesf.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Performance of older adults under dual task during stair descent

Abstract: BackgroundStair walking, especially in dual-task conditions, is a challenging daily routine for older adults. The purpose of this study is to investigate gait and postural control and explore the possible reasons for the fall risk encountered by healthy older adults under dual-task conditions during stair descent.MethodsThirty healthy older female adults (aged 67 ± 1 years, standing height of 1.64 ± 0.17 m, body mass of 66.01 ± 4.27 kg, and education of 8.92 ± 0.95 years) were randomly recruited from local com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…However, there were no significant differences between stair ascent and descent alone compared to dual-tasking with an easy working memory task. Another study revealed that responding to an arithmetic task led to a decline in gait speed between single and dual-tasks during stair descent [ 20 ]. Therefore, gait speed changes may greatly depend on the difficulty of the cognitive task.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there were no significant differences between stair ascent and descent alone compared to dual-tasking with an easy working memory task. Another study revealed that responding to an arithmetic task led to a decline in gait speed between single and dual-tasks during stair descent [ 20 ]. Therefore, gait speed changes may greatly depend on the difficulty of the cognitive task.…”
Section: Discussionmentioning
confidence: 99%
“…This study builds upon previous behavioral work that examined changes in gait speed and response time performance in older adults during stair negotiation [ 17 , 20 ]. The purpose of this study was to evaluate the hemodynamic response (∆HbO2 and ∆HbR) and performance (gait speed, response time and response accuracy) changes in older adults under single and dual-task stair ascent and descent.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In an experimental study on OA aged 65 years and older, VGA was recorded in terms of a transition from a wide to a narrower path. Other studies have used dual-task paradigms during stair climbing to assess VGA [ 20 , 21 ]. There is a considerable body of literature on cognitive tasks affecting VGA [ 22 - 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In modern architecture, particularly social architecture, stairs have become functionally indispensable because of the need to create more useable space through the construction of multi-storey buildings. Stairs are, however, inherently difficult for humans to negotiate and are nearly always associated with the risk of accident (Atlas, 2019;Zhang et al, 2018;Jacobs, 2016;Neary, 2014). Several IJBPA 40,1 20…”
Section: Introductionmentioning
confidence: 99%